Creativity, innovation and implementation: Management experience, venture size, life cycle stage, race and gender as moderators - M. Pretorius; S. M. Millard; M. E. Kruger (South African Journal of Business Management, 2005)
SMME (small, medium and micro-enterprise) development has been identified by the South African government as a priority in creating jobs. The Global Entrepreneurship Monitor reports low entrepreneurial activity and suggests entrepreneurial education as paramount for improvement. Entrepreneurial skills depend on creativity and innovation as it distinguishes the entrepreneur from the small venture owner. This study empirically investigated the perceptions of small venture owners about their own creativity, their ventures' innovativeness as well as their implementation orientation. While levels of self-evaluation for own creativity and venture innovativeness were high, implementation orientation was low and correlations between them were weak and not significant. Notwithstanding the expectation that high creativity will lead to high innovation and implementation, this article reports otherwise.It was found that number of years management experience, life cycle phase of the venture and race (cultural heritage) but not venture size and gender moderate perception of own creativity. Perception of venture innovativeness was significantly influenced by the life cycle phase of the venture only. Implementation orientation was significantly influenced by the number of years management experience, life cycle phase of the venture, venture size and race but not by gender.
Keywords: 650